The Influence of Work Motivation and Work Discipline Through Work Culture on Employee Performance at Ametis Villa Bali - Budiasa, I Ketut; Nugraha, Surya; Pibriari, Ni Putu Widhya (Jurnal Manajemen Pelayanan Hotel, 2023)
The performance of employees at Ametis Villa Bali has a big role in achieving organizational goals, thereforeimproving employee performance is very important to do. There are many factors that can influence employeeperformance, namely work motivation, work discipline and work culture. The aim of this research is todetermine the influence of work motivation and work discipline through work culture on employeeperformance at Ametis Villa Bali. The data in this research was collected using a questionnaire method whichwas distributed to respondents, namely 75 employees at Ametis Villa Bali. The data analysis technique used toachieve the objectives of this research is path analysis which tests the direct and indirect influence betweenvariables. The research results show that (1) work motivation and work discipline have a direct positive andsignificant influence on work culture, (2) work motivation, work discipline and work culture have a directpositive and significant influence on employee performance and (3) work motivation and work discipline hasa significant influence indirectly through work culture on employee performance. It is recommended thatemployees at Ametis Villa Bali be more diligent in their work, honest in their work, be professional and beresponsible for the results of their work.Keywords: Work Motivation, Work Discipline, Work Culture and Employee Performance